Transvaginal Ultrasound for Endometrial Carcinoma Screening – Current Evidence-based Data - Steiner, E.; Juhasz-Bösz, I.; Emons, G.; Kölbl, H.; Kimmig, R.; Mallmann, P.; für die AGO Uterus der DGGG (Geburtshilfe und Frauenheilkunde, 2012)
The value of transvaginal ultrasound in gynaecological examinations is beyond dispute. But it is of particular forensic importance that the validity of this type of imaging with regard to the reliable detection of early-stage malignancy is properly understood. Vaginal ultrasound screening in asymptomatic patients for the early detection of endometrial carcinoma is not useful from a medical point of view, nor is it cost-efficient. However, even though the validity of transvaginal ultrasound for screening has currently not been proven, the method should still be an integral part of gynaecological examinations.
Keywords: transvaginal ultrasound; endometrial cancer; screening